Does Hydroxychloroquine Protect against Preeclampsia and Preterm Delivery in Systemic Lupus Erythematosus Pregnancies? - Do, Samantha C.; Rizk, Nada M.; Druzin, Maurice L.; Simard, Julia F. (American Journal of Perinatology, 2020)
Objective Systemic lupus erythematosus (SLE) increases the risk of complications in pregnancy. Hydroxychloroquine (HCQ) decreases flares and neonatal lupus syndrome. Limited evidence suggests that HCQ also reduces preeclampsia and preterm birth in SLE pregnancies. We studied whether HCQ was associated with lower odds of preeclampsia and preterm delivery in SLE pregnancies.Study Design We conducted a retrospective cohort study of 129 deliveries of 110 patients with SLE delivered at a single institution (2000–2017). HCQ exposure and preeclampsia, along with other clinical data, were extracted from chart review. Crude and multivariable-adjusted logistic regression estimated odds ratios (ORs) and 95% confidence intervals (CIs).Results A total of 41% were exposed to HCQ, of whom 13.5% were complicated by preeclampsia versus 26.3% unexposed to HCQ (adjusted OR = 0.5; 95% CI: 0.2–1.4). The difference was pronounced for first pregnancies (7 vs. 44%), but power was limited. The difference in preterm deliveries was less pronounced comparing HCQ-exposed pregnancies with HCQ-unexposed pregnancies (34 vs. 40.8%; OR = 0.3; 95% CI: 0.3–1.5).Conclusion Pregnant SLE patients trended toward less preeclampsia and preterm delivery when treated with HCQ. Future larger studies are needed to increase the statistical power, account for additional potential confounders, and more fully account for parity.
Keywords: lupus; pregnancy; preeclampsia; preterm; hydroxychloroquine